LUBRICATING MATERIALS AS A NOVEL APPROACH TO REDUCE DEFECTS OF MICRO-DEEP DRAWING FORMING PROCESS - Ibrahim, Zaman; Abdul Ridha, Ghassan; Yousif , Tahseen; Abdullah, Isam; Mohammed, Malik; Alalwan, Hayder (Journal of Applied Engineering Science, 2024)
The deep drawing forming process, classified under sheet metal working, is a promising and essential metal forming process that has attracted much interest due to its wide application in micro-production. The process parameters, such as the cross-head speed of the machine, have a significant influence on the quality of the product. The impact of two essential parameters was investigated to minimize or eliminate the product's production defects, such as thinning, tearing, and scratching. The first one was the impact of using two types of lubricating oil (grease and wax), and the products were compared with the dry condition (without using a lubricating oil). The second is the impact of changing the cross-head speed of the machine from 5 to 15 mm/min. This work aims to determine the optimum operating condition that prevents any defect in the product. The results showed that using lubricating oil resulted in better product shape, and the wax is better than grease in eliminating product defects. In addition, the results showed that the lower machine speed is preferred for eliminating production defects, where the final product has no obvious thinning, tearing, or scratching. The final product shape was evaluated visually because eye observation is the only way to judge the product shape.
Keywords: sheet metal, thinning, tearing, scratching, grease, wax